Dry eye disease and associated factors in Kazakhstan and Uzbekistan - Q. B. Maskati; Sh. Kumar; V. Chaubey; N. Katakwar; S. Sharma (Российский офтальмологический журнал, 2021)
Dry eye disease (DED) is an ocular condition with a high prevalence globally. The survey was conducted to understand factors that influence the treatment of DED in Kazakhstan and Uzbekistan and the properties of artificial tears required in its treatment. Purpose. The survey aimed to understand the prevalence of DED in the population of Kazakhstan and Uzbekistan, whether associated ocular diseases and patient lifestyle affected DED treatment, the properties of artificial tears required in the treatment of DED, and the use of artificial tears in conditions other than DED. Material and methods.A total of 457 ophthalmologists participated in the survey that was conducted between June–July 2019 in selected cities of Kazakhstan and Uzbekistan. The questionnaire assessed the number of patients with DEs, associated ocular diseases, contributing factors to poor adherence to DED treatment, major concerns in DED and properties of artificial tears required in the treatment of DED. Results.About 73 % of the doctors in Kazakhstan and all the doctors in Uzbekistan reported that DE-associated ocular diseases and lifestyle of a patient contribute to poor adherence to DED therapy. Doctors in Kazakhstan and Uzbekistan ranked hydration at 1.613 and 1.928, respectively, while considering the properties of artificial tears required for the treatment of DED. Conclusion.A majority of the doctors in Kazakhstan and Uzbekistan considered DE-associated ocular diseases and patient lifestyle as major contributing factors to poor adherence to DED treatment. Doctors from both countries considered hydrating property of artificial tears to be the most important ones for the management of DE.